Genetic variation in vitamin D receptor gene (Fok1:rs2228570) is associated with risk of coronary artery disease - Abu El Maaty, Mohamed A.; Hassanein, Sally I.; Gad, Mohamed Z. (Biomarkers, 2016)
Objective: The Fok1 polymorphism (rs2228570) in vitamin D receptor gene appears to be the only polymorphism influencing size of translated protein. Investigations into its association with coronary artery disease (CAD) are sparse.Methods: Male patients (n = 98) with verified CAD were recruited alongside age- and sex-matched controls (n = 55). Genotyping was performed by PCR-RFLP and plasma 25-Hydroxyvitamin D levels were assessed by HPLC-UV.Results: The C-variant (mutant) was predominantly expressed in patients compared to controls (68.9% versus 55.5%; p = 0.025). The observed genotypes were not associated with 25-Hydroxyvitamin D levels.Conclusion: This study presents Fok1 polymorphism as a potential genetic marker for CAD.
Published online: 08 Dec 2015
Gesehen am 14.10.2020